2017
DOI: 10.1002/1873-3468.12585
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of the pLG72 R30K substitution in schizophrenia susceptibility

Abstract: In the human brain, pLG72 interacts with the flavoenzyme d-amino acid oxidase (hDAAO), which is involved in catabolism of d-serine, a co-agonist of N-methyl-d-aspartate receptors (NMDAR). Here, we investigated the wild-type pLG72, the R30K variant associated with schizophrenia susceptibility, and the K62E variant. The protein conformation, oligomeric state, ligand-, and hDAAO-binding properties are only slightly modified by the substitutions. All pLG72 variants inhibit hDAAO and lead to an increase in cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…These ligands do not alter the far-UV CD spectrum of the flavoenzyme (not shown). Notably, we previously demonstrated that pLG72, the specific hDAAO modulator (Sacchi et al, 2008 ), also interacts with nucleotide triphosphates although no ATPase/GTPase activity was assayed (Sacchi et al, 2017 ). Indeed, hDAAO activity on D-alanine (at 2 or 28 mM final concentration) is not modified by the simultaneous presence of 10 mM magnesium ions and ATP or GTP (10 μM).…”
Section: Resultsmentioning
confidence: 99%
“…These ligands do not alter the far-UV CD spectrum of the flavoenzyme (not shown). Notably, we previously demonstrated that pLG72, the specific hDAAO modulator (Sacchi et al, 2008 ), also interacts with nucleotide triphosphates although no ATPase/GTPase activity was assayed (Sacchi et al, 2017 ). Indeed, hDAAO activity on D-alanine (at 2 or 28 mM final concentration) is not modified by the simultaneous presence of 10 mM magnesium ions and ATP or GTP (10 μM).…”
Section: Resultsmentioning
confidence: 99%
“…In past years, we produced recombinant wild-type, R30K (the SNP associated with schizophrenia susceptibility), and the K62E variant of pLG72 (SNP rs9558562) in E. coli cells as inclusion bodies, reaching ≈100 mg/L of fermentation broth (Molla et al, 2006a ; Sacchi et al, 2017 ). In all cases, the recombinant pLG72 proteins were refolded using the anionic detergent N-lauroylsarcosine, a reducing agent and at a basic pH-value.…”
Section: Biochemical Properties Of Plg72mentioning
confidence: 99%
“…Correctly folded pLG72 showed an absorbance maximum centered at 267 nm. The detergent affects the oligomeric state of pLG72: the protein was monodispersed at a detergent concentration ≥0.025%; under optimal conditions, all the pLG72 variants were dimeric (Molla et al, 2006a ; Sacchi et al, 2017 ). The substitutions R30K and K62E only slightly modified the protein conformation, yielding a moderately more rigid conformation than for the previous one (T m was 3–8°C higher than that of wild-type pLG72).…”
Section: Biochemical Properties Of Plg72mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, by applying low-resolution techniques (i.e., limited proteolysis couple to mass spectroscopy and cross-linking experiments) structural determinants of the proteins involved in the formation of the interface surface in the complex could be mapped. This study proposed a model of the hDAAO-pLG72 complex in which the N-terminal region of the protein plays an important role in forming the oligomerization interface (Birolo et al, 2016 ; Sacchi et al, 2017 ). Binding of pLG72 to hDAAO in vitro does not alter the kinetic parameters on D-Ser and the affinity for the FAD cofactor of hDAAO but rather increases the rate of hDAAO inactivation.…”
Section: Modulation Of Hdaao Properties By Interaction With Other Promentioning
confidence: 99%